High-order-harmonic generation from molecular isomers with midinfrared intense laser pulses - Le, Anh-Thu; Lucchese, R. R.; Lin, C. D. (My University, 2013)
We present theoretical calculations of high-order-harmonic generation (HHG) from stereoisomers of 1,2-dichloroethylene (C2H2Cl2) and 2-butene (C4H8) based on the quantitative rescattering theory. Our results show that the HHG spectra from these cis and trans isomers with intense midinfrared laser pulses are clearly distinguishable, even when the molecules are randomly oriented, in good agreement with the recent experiments by Wong et al. [Phys. Rev. A 84, 051403(R) (2011)]. We found that the angle-averaged tunneling ionization yields and photoionization cross sections from the cis and trans isomers for both molecules are nearly identical. The origin of the differences in HHG spectra is traced as due to the interplay in the angular dependence of the photoionization (or photorecombination) cross section and ionization rate.